Sinla lumad an ethnographic documentation of activities and space use of the artists, weavers, & craftsmen in Bukidnon ethnic communities - Bebelone, Ellen Marie R. (2015)
Bukidnon, a province in Northern Mindanao, is rich in visual arts by its indigenous peoples. These visual arts are expressions of human cultural heritage. Through time, this cultural heritage is taking a developing route which must be safeguarded for its genuine beauty and the Lumad cultural identity it upholds. One way to safeguard dynamically these beautiful cultural expressions is through architecture. An important characteristic of architectural space is man?s partaking of life in it. Space definition not only involves physical features but also deals with the cultural capital for human development. This study applied exploratory investigative-method on the transcendent aspects of space by using the concepts of integrating ethnography to the field of architecture. Apart from the physical aspects, these built environments were analyzed with respect to its users ? the artists & craftsmen, their activity processes ? visual arts and crafts making, and their indigenous tools. Data were derived from ethnographic methods which include participant observation, photo and video documentation, semi-structured qualitative interviews, narrative and focus group interviews, field notes, and rough sketches of activity mapping and spatial layouts with dimensions. This research contributed to the knowledge of comprehending and describing space more than its physical form. Since activities and function are expressions of culture, this approach gives importance of the role of culture both in analyzing and designing spaces and built environments. Insights were derived from the data gathered, thus leading to a set of guidelines. With the goal of safeguarding cultural heritage, these set of guidelines were then applied to the project development of this study ? the design of a cultural park.